Opioid overdose prevention education in Texas during the COVID-19 pandemic - Charles W. Mathias; Diana M. Cavazos; Kelly McGlothen-Bell; Allison D. Crawford; Brieanna Flowers-Joseph; Zhan Wang; Lisa M. Cleveland (BMC, 2023)
Abstract Background Distribution of naloxone and training on its proper use are evidence-based strategies for preventing opioid overdose deaths. In-person naloxone training was conducted in major metropolitan areas and urban centers across Texas as part of a state-wide targeted opioid response program. The training program transitioned to a live, virtual format during the COVID-19 public health emergency declaration. This manuscript describes the impact of this transition through analyses of the characteristics of communities reached using the new virtual training format. Case presentation Training participant addresses were compared to county rates of opioid overdose deaths and broadband internet access, and census block comparison to health services shortages, rural designation, and race/ethnicity community characteristics. Conclusions The virtual training format reached more learners than the in-person events. Training reached nearly half of the counties in Texas, including all with recent opioid overdose deaths. Most participants lived in communities with a shortage of health service providers, and training reached rural areas, those with limited broadband internet availability, and majority Hispanic communities. In the context of restrictions on in-person gathering, the training program successfully shifted to a live, online format. This transition increased participation above rates observed pre-pandemic and reached communities with the need for equipping those most likely to witness an opioid overdose with the proper use of naloxone.